2011
DOI: 10.1007/s00223-011-9534-9
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Body Composition and Sex Hormones with Quantitative Ultrasound Parameters at the Calcaneus and Phalanxes in Elderly Women

Abstract: We investigated the associations of body composition and sex hormones with quantitative ultrasound (QUS) parameters carried out at different skeletal sites. In 897 postmenopausal women (64.1 ± 6.6 years) we measured QUS at the calcaneus (stiffness) by Achilles-GE and at phalanxes (amplitude-dependent speed of sound [AD-SOS], bone transmission time [BTT], and ultrasound bone profile index [UBPI]) by Bone Profiler-IGEA. In all subjects we measured fat mass (FM), lean mass (LM), android fat, and gynoid fat by DXA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
1
3
1
2
Order By: Relevance
“…The skeleton responds to mechanical loading by increasing its mass [ 42 ]. Thus, higher BMD values or QUS indices in subjects with higher BMI was a common finding in previous epidemiological studies [ 26 , 27 , 43 , 44 ]. However, BMI is not the most accurate obesity index [ 45 ].…”
Section: Discussionsupporting
confidence: 59%
“…The skeleton responds to mechanical loading by increasing its mass [ 42 ]. Thus, higher BMD values or QUS indices in subjects with higher BMI was a common finding in previous epidemiological studies [ 26 , 27 , 43 , 44 ]. However, BMI is not the most accurate obesity index [ 45 ].…”
Section: Discussionsupporting
confidence: 59%
“…But, except DHEAS and FT, none of the alternatively measured sex hormones were associated with bone ultrasound parameters. In contrast to our results, previous studies among post-menopausal women reported positive association of DHEAS with SI ( Hosoda et al, 2008 ) and an association of estradiol with QUS ( Gonnelli et al, 2011 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research suggested a potential link between sex hormones and bone metabolism ( Venken et al, 2008 ). Exemplarily, estrogen and dehydroepiandrosterone sulphate (DHEAS) exposure in adolescence have been related to skeletal maturation and bone mineral density, same as estrogen deficiency and decreasing sex hormone concentrations to bone loss ( Dhuper et al, 1990 , Porcu et al, 1994 , Gonnelli et al, 2011 ). Beside well-established risk factors for osteoporosis, including aging, female sex, pre-existing fractures and physical inactivity, previous experimental research suggests a bi-directional link between sex hormones and bone metabolism ( Oury et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…This might contribute to bone loss, in part, due to the direct effect of reduced soft-tissue mass on bone through reduced mechanical loading (Martin 2007). Additionally, decreased fat tissue might lead to reductions in aromatase activity, which lowers the production of estradiol and consequently increases bone turnover (Gonnelli et al 2011, Liu et al 2014. The decrease in estradiol in women with canagliflozin is consistent with this hypothesis (Bilezikian et al 2016).…”
Section: Selective Inhibitor Of Sodium-glucose Cotransporter-2mentioning
confidence: 77%